Quality control in the production of radiopharmaceuticals. (IAEA-TECDOC, 2018)
Radiopharmaceuticals are central to nuclear medicine applications for the diagnosis and therapy of human diseases, especially cancers and cardiovascular diseases. In the past few decades, advances in the production and quality control of emerging radiopharmaceuticals have led to the production of new radiopharmaceuticals and the availability of new production routes and methods for existing agents. Various new diagnostic agents in the field (such as 68Ga radiopharmaceuticals and generators) as well as therapeutic agents (such as alpha emitters) have already been added to the clinician toolkit. However, the lack of generic and peer-reviewed quality control guidelines and recommendations for their application in human patients is a major concern. To address this need, and in response to requests from Member States and professional societies, the IAEA developed this publication on quality control in the production of radiopharmaceuticals. It is expected to be of use for all professionals involved in the production and quality control of radiopharmaceuticals worldwide.